The effect of tapioca starch concentration on mechanical properties of Sansevieria Trifasciata fiber-reinforced composites - Misbakh; Edi Widodo; Iis Siti Aisyah; Syahruddin; Nur Haizal Ariffin (University of Muhammadiyah Malang, 2024)
This research investigates the impact of varying concentrations of tapioca starch (Manihot esculenta) on the mechanical properties of composites reinforced with Sansevieria trifasciata (Lidah mertua) fibers. The composites were fabricated using the hand lay-up method with SHCP 2668 polyester resin, mekpo catalyst, and alkali-treated fibers (5% NaOH). The fiber weight fraction was 30%, and the catalyst weight was 10% of the total specimen mass. The tapioca starch concentrations were 0%, 10%, 20%, 30%, 40%, and 50%, with a total matrix mass of 50 grams. Mechanical properties were evaluated through tensile tests (ASTM-D3039) and bending tests (ASTM-D790). The results indicated that composites with added tapioca starch exhibited improved tensile strength and a higher modulus of elasticity. However, for bending tests, the composites without added tapioca starch demonstrated better performance, showing a higher elastic modulus and better flexibility. In conclusion, adding tapioca starch enhances the tensile strength of the composites, making them stronger. Conversely, for bending applications, composites without tapioca starch are preferable due to their superior elasticity and bending strength.